Comparison of the retentive ability on incisal bite force between aloe vera and poly(methyl-vinyl-ether) adhesive materials in complete acrylic denture measured by modified pressure transducer - Julinda, Marisa; Sumarsongko, Taufik; Alamsyah, Gian Nur; Adenan, Aprillia (Universitas Padjadjaran, 2021)
Introduction: Patients with acrylic complete denture, usually have a confidence issue in using their complete dentures to chew and speak, because of concern about detached of the denture from its place and pain on the alveolar ridge. Application denture adhesive material ordinarily can solve the problem. Mostly, denture adhesives in the market are made from synthetic material poly(methyl-vinyl-ether) but nowadays aloe vera extract is believed to be a substitute to synthetic denture adhesive material. The purpose of this study was to analyzed of comparison the retentive ability on incisal bite forces between aloe vera extract and poly(methyl-vinyl-ether) adhesive in complete acrylic denture ameasured by modified pressure tranducer. Methods: This true-experimental research used 10 samples from patients who used acrylic complete denture and meet suitable criteria. Samples were tested in three different interventions, the first one applied by denture adhesive made from poly(methyl-vinyl-ether), the second one applied by denture adhesive made from aloe vera extract and the third one as a control group, sample was tested without any application of denture adhesive. Retentive ability on incisal bite forces was measured by modified pressure transducer with integrated software. Data was analysis using ANOVA method. Results: Anterior bite force as control 20,98 N, aloe vera 23,42 N, poly (methyl-vinyl-ether) 21,25 N and without denture adhesive as control. Significant differences in the incisal bite force dislodgement of dentures that were applied with Aloe vera-based denture adhesive s with p-value of 0.0088. Conclusion: Denture adhesive made from Aloe vera extract had the highest adhesiveness incisal bite force value compared to denture adhesive made from poly(methyl-vinyl-ether) and without denture adhesive.